2013
DOI: 10.1186/1745-6215-14-318
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a multifaceted intervention on cardiovascular risk factors in high-risk hypertensive patients: the ESCAPE trial, a pragmatic cluster randomized trial in general practice

Abstract: BackgroundSeveral observational studies on hypertensive patients have shown a gap between therapeutic targets recommended in guidelines and those achieved in daily practice. The ESCAPE trial aimed to determine whether a multifaceted intervention focused on general practitioners (GPs), could increase significantly the proportion of hypertensive patients at high risk in primary prevention who achieved all their recommended therapeutic targets.MethodsA pragmatic, cluster randomized trial involving 257 GPs randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
1
7
1
Order By: Relevance
“…Third, the BP changes observed in our study are within the range of those observed in other CRTs (Figure 1). Like ours, all studies saw improvements in BP within their study populations, but with inconsistent interventional effects (5,6,9,10,14,15).…”
Section: Changes In Practice Management and Medicationsupporting
confidence: 51%
See 1 more Smart Citation
“…Third, the BP changes observed in our study are within the range of those observed in other CRTs (Figure 1). Like ours, all studies saw improvements in BP within their study populations, but with inconsistent interventional effects (5,6,9,10,14,15).…”
Section: Changes In Practice Management and Medicationsupporting
confidence: 51%
“…While the majority of these interventions used rather costly external support structures, few randomized studies combined internal practice redesign with educational strategies (14,15): Reuther et al (2012) combined physician education about clinical management and practice organization with a clinical decision support system, benchmarking, peer audits, and a specialist hotline: After a 24-month follow-up in 2646 patients from 124 practices, the interventional effects amounted to -1.75 mmHg systolic [95% confidence interval (CI) 4.02 to 0.53] and +0.14 mmHg diastolic [95% CI: -1.16 to 1.44] (15).…”
mentioning
confidence: 99%
“…The inclusion criteria and a description of the intervention have been detailed elsewhere [7]. Practitioners in the IG were supplied with a validated electronic device to measure BP (Spengler TB 101; Spengler SAS, Antony, France).…”
Section: Methodsmentioning
confidence: 99%
“…ESCAPE (EffetS d'une intervention multifaCtorielle sur les fActeurs de risque des patients hyPErtendus) was a pragmatic cluster randomized-controlled trial [7]. Its primary aim was to show that a multifactorial intervention targeting general practitioners increased the number of high cardiovascular risk hypertensive patients in primary prevention achieving the recommended targets [8] without altering their quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…introduced calibrated 24-hour blood pressure monitor devices in primary care practices, while Reuther et al . introduced strategies to organize hypertension management in primary care [ 23 , 24 ]. The mean group differences were −4.76/-1.88 mmHg [ 23 ] and −1.75/+0.14 mmHg [ 24 ].…”
Section: Discussionmentioning
confidence: 99%